ChemInform Abstract: Directed Lithiation of Simple Aromatics and Heterocycles for Synthesis of Substituted Derivatives. Issue 25 (5th June 2015) - El‐Hiti, Gamal A.; Smith, Keith; Hegazy, Amany S.; Alshammari, Mohammed B.; Masmali, Ali M.
Abstract: Review: 225 refs.